Risk factors for RhD immunisation in a high coverage prevention programme of antenatal and postnatal RhIg: a nationwide cohort study. (18th March 2022) - Slootweg, Y. M.; Zwiers, C.; Koelewijn, J. M.; van der Schoot, E.; Oepkes, D.; van Kamp, I. L.; de Haas, M.
Abstract: Objective: To evaluate which risk factors for RhD immunisation remain, despite adequate routine antenatal and postnatal RhIg prophylaxis (1000 IU RhIg) and additional administration of RhIg. The second objective was assessment of the current prevalence of RhD immunisations. Design: Prospective cohort study. Setting: The Netherlands. Population: Two‐year nationwide cohort of alloimmunised RhD‐negative women. Methods: RhD‐negative women in their first RhD immunised pregnancy were included for risk factor analysis. We compared risk factors for RhD immunisation, occurring either in the previous non‐immunised pregnancy or in the index pregnancy, with national population data derived from the Dutch perinatal registration (Perined). Results: In the 2‐year cohort, data from 193 women were eligible for analysis. Significant risk factors in women previously experiencing a pregnancy of an RhD‐positive child ( n  = 113) were: caesarean section (CS) (OR 1.7, 95% CI 1.1–2.6), perinatal death (OR 3.5, 95% CI 1.1–10.9), gestational age >42 weeks (OR 6.1, 95% CI 2.2–16.6), postnatal bleeding (>1000 ml) (OR 2.0, 95% CI 1.1–3.6), manual removal of the placenta (MRP) (OR 4.3, 95% CI 2.0–9.3); these factors often occurred in combination. The miscarriage rate was significantly higher than in the Dutch population (35% versus 12.‐5%, P  < 0.001). Conclusion: Complicated deliveries, including cases of major bleeding and surgical interventions (CS, MRP), must be recognised as a risk factor, requiring estimation of fetomaternal haemorrhage volume and adjustment of RhIg dosing. The higher miscarriage rate suggests that existing RhIg protocols need adjustment or better compliance. Tweetable abstract: Complicated delivery (caesarean section, manual removal placenta, major bleeding) is the most valid risk factor for RhD immunization despite antenatal and postnatal RhIg. Tweetable abstract: Complicated delivery (caesarean section, manual removal placenta, major bleeding) is the most valid risk factor for RhD immunization despite antenatal and postnatal RhIg.